MARINE CRIME IN INDONESIA: A SPATIO-TEMPORAL ASSESSMENT OF EMERGING TRENDS AND HOTSPOTS - Kurniawan, Rahmad; Manessa, Masita Dwi Mandini; Golkariansyah; Wiratama, Eska Yosep; Budiman, Asep (BRIN, 2024)
Indonesia, with its vast maritime domain, faces significant challenges related to maritime crime, including illegal, unreported, and unregulated (IUU) fishing, piracy, human trafficking, and smuggling. The country’s strategic position, bordering key shipping routes like the Strait of Malacca and the Sunda Strait, exacerbates its vulnerability to transnational crimes. This study provides a spatio-temporal assessment of emerging trends and hotspots of marine crime in Indonesia during the period of 2022-2023. Through an analysis of crime incidents, the research identifies key areas of concern, such as the Java Sea, Sumatra, and Eastern Indonesia, where illegal activities have shown persistent and intensifying patterns. The Strait of Malacca and Aceh emerged as critical zones, with increased incidents of piracy and human trafficking, partly linked to the Rohingya refugee crisis. Additionally, the study highlights the environmental impact of illegal activities in ecologically sensitive regions, such as Papua and the Coral Triangle, where illegal logging, mining, and destructive fishing practices threaten marine ecosystems. The analysis also reveals seasonal trends, with the highest concentration of incidents occurring between July and September, coinciding with peak fishing activities. Despite efforts by the Indonesian government, including the Sinking of Foreign Vessels Policy and regional cooperation initiatives like ReCAAP, enforcement gaps remain, particularly in remote regions. The study identifies critical gaps in maritime security, including the need for improved technological surveillance and enhanced community engagement in enforcement efforts. The findings underscore the importance of spatial-temporal monitoring to inform targeted law enforcement and policy responses, thereby protecting Indonesia’s marine resources and enhancing national security.